Stimulus affective valence reverses spatial compatibility effect - Conde,Erick Francisco Quintas (2011)
In spatial compatibility tasks, the Reaction Time to right-side stimuli is shorter for right key responses (compatible condition) than for left key responses (incompatible condition) and vice-versa for left-side stimuli. Similar results have been found when the stimulus location is not relevant for response selection, such as in the Simon task. The Simon effect is the difference between the reaction times for non-corresponding and corresponding conditions. The Simon effect and its variants may be modulated by using emotional stimuli. However, until now, no work has studied how the affective valence of a stimulus influences spatial compatibility effects along the horizontal dimension. The present study investigated this issue by using small lateralized figures of soccer team players as stimuli. In the experiment, a compatible or incompatible response was chosen according to the team shirt. In one block, for the Favorite team, the volunteers had to press the key on the same side as the stimulus hemifield but the opposite-side key for the Rival team. In the other block, a reverse code had to be used. Fourteen right-handed volunteers were tested. Mean reaction times were subjected to analysis of variance with the following variables: Preference (Favorite/Rival), Hemifield (Left/Right), and Response Key (Left/Right). A three-way interaction was found (F1,13 = 6.60, p = .023), showing that the spatial compatibility effects depended on Preference. The Favorite team player elicited the usual spatial compatibility pattern, but for the Rival team player, the reverse effect was found, with incompatible responses being faster than compatible responses. We propose that this modulation may result from approach/avoidance reactions to the Favorite and Rival teams, respectively. Moreover, we suggest as a corollary that the classic spatial compatibility task is a powerful tool for investigating approach/avoidance effects.